El endemismo en la flora fanerogámica de la Mixteca Alta, Oaxaca‑Puebla, México - Garcia-Mendoza, Abisai; Tenorio Lezama, Pedro; Reyes Santiago, Jeronimo (Instituto de Ecología, A.C., 1994)
The Mixteca Alta region is located at the junction of NW part of the state of Oaxaca and the S of Puebla. It is covered primarily by Pinus and Quercus forest and chaparral with small areas of tropical deciduous forest and cloud forest. Its flora is estimated in 1550 indigenous species; 163 (10.5%) of them are endemic, 97 (59.5%) of these are restricted to the Mixteca Alta, 50 (30.7%) extend their distribution area farther west into Oaxaca, and 16 (9.8%) farther east into Guerrero. Thirty-four families and 92 genera present endemic taxa. Ainea (a monotipic genus) is endemic to Mixteca Alta, while Fosteria, Gibasoides and Pseudocranichis extend lightly outside this limit. The life forms in the endemic element consist of 52% herbaceous plants, 20% succulents, 17% shrubs, 4% climbers, 6% of creeping and epiphytes, and 1% trees. Given our present knowledge of the flora we estimate that about 15-20% of the species are still uncollected. In this paper a list of the endemic taxa is included, with information about their distribution, life forms and the political districts in which they occur.